2014
DOI: 10.18869/acadpub.jhs.2.3.15
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Health-risk Behaviors of Boys and Girls of Freshmen Year at Tehran University, Iran

Abstract: Background and purpose: Priority health-risk behaviors, often are established during childhood and adolescence, extend into adulthood, and are interrelated and preventable. This study was conducted to determine and compare the prevalence of risky behaviors on both sexes of freshman students enrolled in Tehran University, Iran. Materials and Methods: This study was a descriptive-analytical type of cross-sectional survey which has used stratified sampling to select 432 students during 2011-2012. A questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…The results of a study among students in Khorramabad, Iran, showed that the prevalence rates of smoking cigarette, drug abuse, and alcohol consumption were 3.7%, 2.4%, and 5.5%, respectively [27]. Another study conducted on Tehran University students showed that the prevalence rates of alcohol, drug abuse, and high-risk sexual behaviors were 4.6%, 2.3%, and 5.6%, respectively [28]. Another study on the prevalence of high-risk behaviors among students in Rudan, Iran, demonstrated that the prevalence rates of drug use, alcohol consumption, and high-risk sexual behaviors were 5.5%, 4.9%, and 6.6%, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study among students in Khorramabad, Iran, showed that the prevalence rates of smoking cigarette, drug abuse, and alcohol consumption were 3.7%, 2.4%, and 5.5%, respectively [27]. Another study conducted on Tehran University students showed that the prevalence rates of alcohol, drug abuse, and high-risk sexual behaviors were 4.6%, 2.3%, and 5.6%, respectively [28]. Another study on the prevalence of high-risk behaviors among students in Rudan, Iran, demonstrated that the prevalence rates of drug use, alcohol consumption, and high-risk sexual behaviors were 5.5%, 4.9%, and 6.6%, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of alcohol and illicit drug use in the same group during the lifetime was found to be 11.9% and 8.8%, respectively (Afrashteh, Ghaem, Abbasi‐Ghahramanloo, & Tabatabaee, 2017). Although the prevalence of high‐risk sexual behaviours is controversial in the Iranian context, some studies reported extramarital sexual relationships among Iranian youth to be about 8%–41% (Mahmoodi et al, 2019; Rahmati‐Najarkolaei & Kamalikhah, 2014; Vakilian, Mousavi, & Keramat, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Among Iranian students, the prevalence of substance use is relatively high. 2,5 For example, in a study conducted in six universities in Tehran, a relatively high prevalence of hookah, smoking and alcohol use was reported. 9 Important factors contributing to substance use include gender, high stress, the family history of substance use, family conflicts and protective factors such as religion, parental support and the high level of parental education.…”
Section: Introductionmentioning
confidence: 99%
“…In the 21st century, adolescents and youths have encountered multiple social changes that may contribute to potential substance use. 2 One of the most important stages in the lives of these young adults can occur when they enter a university, which is associated with separation from family, facing peer pressures and exposure to new experiences, in turn leading to increased stress and behavioral problems such as substance use. Substance use can result in physical injuries and irreparable educational, psychological, socioeconomic and occupational failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation